Genome-wide identification of the C2H2 zinc finger gene family and expression analysis under salt stress in sweetpotato - Du, Taifeng; Zhou, Yuanyuan; Qin, Zhen; Li, Aixian; Wang, Qingmei; Li, Zongyun; Hou, Fuyun; Zhang, Liming (Frontiers in Plant Science, 2023)
The higher plant transcription factor C2H2 zinc finger protein (C2H2-ZFP) is essential for plant growth, development, and stress response. There are limited studies on C2H2-ZFP genes in sweetpotato, despite a substantial number of C2H2-ZFP genes having been systematically found in plants. In this work, 178 C2H2-ZFP genes were found in sweetpotato, distributed randomly on 15 chromosomes, and given new names according to where they were located. These members of the zinc finger gene family are separated into six branches, as shown by the phylogenetic tree. 24 tandem repeats of IbZFP genes and 46 fragment repeats were identified, and a homology study revealed that IbZFP genes linked more regions with wild relative species of sweetpotato as well as rhizome plants like potato and cassava. And we analyzed the expression patterns of IbZFP genes during the early development of sweetpotato storage roots (SRs) and salt stress using transcriptome data, and identified 44 IbZFP genes that exhibited differences in expression levels during the early expansion of sweetpotato SRs in different varieties, and 92 IbZFP genes that exhibited differences in expression levels under salt stress in salt tolerant and salt sensitive sweetpotato varieties. Additionally, we cloned six IbZFP genes in sweetpotato and analyzed their expression patterns in different tissues, their expression patterns under abiotic stress and hormone treatment, and subcellular localization. The results showed that the IbZFP genes had tissue specificity in sweetpotato and were induced to varying degrees by drought and salt stress. ABA and GA3 treatments also affected the expression of the IbZFP genes. We selected IbZFP105, which showed significant differences in expression levels under salt stress and ABA treatment, to be heterologously expressed in Arabidopsis thaliana. We found that IbZFP105 OE lines exhibited higher tolerance to salt stress and ABA stress. This indicates that IbZFP105 can enhance the salt tolerance of plants. These results systematically identified the evolution and expression patterns of members of the C2H2-ZFP gene family in sweetpotato, providing a theoretical basis for studying the role of IbZFP genes in the development of sweetpotato SRs and in resistance to stress.